Dilemma in pediatric mandible fractures: Resorbable or metallic plates? - Filinte, Gaye Taylan; Akan, İsmail Mithat; Çardak, Gülçin Nujen Ayçiçek; Mutlu, Özay Özkaya; Akoz, Tayfun (Turkish Association of Trauma and Emergency Surgery, 2015)
BACKGROUND: The aim of this study was to compare the efficiency of resorbable and metallic plates in open reduction and internal fixation of mandible fractures in children. METHODS: Thirty-one patients (mean age, 8.05 years; range 20 months-14 years) were operated on various fractures of the mandible (26 [60.4%] symphysis-parasymphysis, 12 [27.9%] condylar-subcondylar fractures, 5 [11.6%] angulus and ramus fractures). Twelve patients were treated with resorbable plates and 19 patients with metallic plates. Mean follow-up time was 41 months (11-74 months) in the metallic hardware group and was 22 months (8-35 months) in the resorbable plate group. Both groups were investigated for primary bone healing, complications, number of operations, and mandibular growth. The results were discussed below. RESULTS: Both groups demonstrated primary bone healing. Minor complications were similar in both groups. The metallic group involved secondary operations for plate removal. Mandibular growth was satisfactory in both groups. CONCLUSION: Resorbable plates cost more than the metallic ones; however, when the secondary operations are included in the total cost, resorbable plates were favourable. As mandibular growth and complication parameters are similar in both groups, resorbable plates are favored due to avoidance of potential odontogenic injury, elimination of long-term foreign body retention and provision of adequate stability for rapid bone healing. However, learning curve and concerns for decreased stability against heavy forces of mastication accompanied with the resorbable plates when compared to the metallic ones should be kept in mind.

AMAÇ: Bu çalışmanın amacı çocuklardaki açık redüksiyon ve internal fiksasyon ile tedavi edilen mandibula kırıklarında, emilebilen ve metal plakların etkinliğini karşılaştırmaktır. GEREÇ VE YÖNTEM: Yaşları 20 ay-14 yıl (ortalama 8.05 yıl) arasında değişen 31 hasta mandibulanın farklı yerlerindeki kırıklar nedeniyle ameliyat edildi (26 [%60.4] simfisiz-parasimfisiz, 12 [%27.9] kondil-subkondil, 5 [%11.6] angulus ve ramus). On iki hasta eriyen plaklarla, 19 hasta ise metal plaklarla (titanyum) tedavi edildi. Ortalama takip süresi metal donanım kullanılan grupta 41 ay (11–74 ay), eriyen plak kullanılan grupta ise 22 ay’dı (8–35 ay). Her iki grup primer kemik iyileşmesi, komplikasyonlar, ameliyat sayısı ve mandibuladaki büyüme açısından incelendi. Bulgular aşağıda tartışıldı. BULGULAR: Her iki grupta primer kemik iyileşmesi saptandı. Her iki gruptaki minör komplikasyonlar benzerdi. Metal donanım kullanılan grupta pak çıkartılması için ikinci operasyonlar gerçekleştirildi. Her iki gruptaki mandibula gelişimi tatmin ediciydi. TARTIŞMA: Eriyen plaklar metal donanımlı plaklardan daha pahalı oldukları görüldü. İkinci operasyonların maliyeti göz önünde bulundurulduğunda ise eriyen plaklar daha avantajlıydı. Mandibula büyümesi ve komplikasyon parametreleri heriki grupta benzer olduğundan, eriyen plaklar; olası diş hasarının önlenmesi, uzun süreli yabancı cisim varlığının olmaması ve hızlı kemik iyileşmesi için gerekli olan yeterli sabitlik sağlaması gibi hususlara bağlı olarak tercih edilmektedir. Buna rağmen, emilebilir plakların kullanılması hususunda bir öğrenme periyodunun gerekliliği ve metal plaklarla karşılaştırıldığında, çiğneme kaslarının karşıt gücüne karşı düşük sabitlik sağladıkları gibi endişeler akılda tutulmalıdır.
Pediatrik mandibula kırıklarındaki ikilem: Eriyen plaklar mı yoksa metal plaklar mı?
WOS: 000368269100015
PubMed ID: 27054644
Keywords: Mandibular Fractures; Metallic Plates; Resorbable Plates; Eriyen Plaklar; Mandibula Kırıkları; Metal Plaklar